Customs, Brokers, and Informal Sectors : A Cameroon Case Study - Cantens, Thomas (World Bank, Washington, DC, 2014)
Based on extensive interviews with informal importers and brokers in Cameroon, this paper explains why customs reform aimed at reducing fraud and corruption may be difficult to achieve. Informal traders and brokers (without licenses) follow various business models and practices, which are product-specific. Overall, what matters first are customs brokers' practices. Information asymmetries mark transactions between brokers and importers and are accompanied by misperceptions of the costs and risks of informal brokers working among informal importers. In a low-governance environment with widespread informal practices, blanket policies should be avoided in order to discourage activities of unprofessional and systematic bribe-taker brokers. It is also essential that customs officials disrupt information asymmetries and better disseminate information to informal importers on customs processes and official costs. Finally, customs should more strongly sanction some informal brokers in order to reduce collusion with some customs officers.